Multidimensional scaling applied to studies of musical appreciation - Silva, Raquel Cocenas da; Bueno, José Lino Oliveira; Bigand, Emmanuel; Molin, Paul (Paidéia (Ribeirão Preto), 2009)
The multidimensional scaling (MDS) originates from a set of techniques for analyzing proximity of data, which is obtained through the judgments of participants who concomitantly compare several stimuli in various dimensions. The analysis of proximity judgments produces an analysis in which points represent the relationship existent between stimuli in a Euclidean space. The configuration of stimuli in the space defined by these dimensions permits to make inferences about the underlying perceptual universe of the studied group. Literature reveals that MDS is enlarging the study of music and the measurement of its structural properties.